2022
DOI: 10.22190/fupes220225007t
|View full text |Cite
|
Sign up to set email alerts
|

Can a Physical Activity Programme Improve the Quality of Life in Youth Who Live in an Orphanage? A Mixed Methods Study

Abstract: Physical activity (PA) is thought to positively contribute to the improvement of the (poor) Quality of Life (QoL) of youth living in institutions. However, youth’s participation in PA can be affected by the “significant others” in their life. The aim of this study was to (a) investigate the impact of a PA programme on the QoL of youth hosted in an orphanage and (b) understand the role of the relationships formed in this institution in the outcome of the programme objectives. For that purpose, a mixed methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Based on the results obtained in Table 3, the results show that the respondents strongly agree (45.56%) that they are always involved with activities organized by outsiders, for example, non-profit organizations, universities/colleges, and companies. Trampa and Venetsanou (2022) revealed that physical activity organized at the orphanages has positive implications for the quality of life of youth. World Health Organization (WHO, 2019) explained that quality of life is important for individual and public health to support the well-being of people.…”
Section: Social Engagementmentioning
confidence: 99%
“…Based on the results obtained in Table 3, the results show that the respondents strongly agree (45.56%) that they are always involved with activities organized by outsiders, for example, non-profit organizations, universities/colleges, and companies. Trampa and Venetsanou (2022) revealed that physical activity organized at the orphanages has positive implications for the quality of life of youth. World Health Organization (WHO, 2019) explained that quality of life is important for individual and public health to support the well-being of people.…”
Section: Social Engagementmentioning
confidence: 99%